1983
DOI: 10.1128/iai.42.2.716-720.1983
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular dextranase activity produced by human oral strains of the genus Bifidobacterium

Abstract: Three strains of anaerobic, dextranase-producing, gram-positive, rod-shaped bacteria were isolated from human dental plaque associated with root carious lesions. The isolates produced a molar ratio of acetate to lactate from glucose fermentation ranging from 1.1 to 1.9. Each strain also produced fructose-6phosphate phosphoketolase. The isolates were identified as belonging to the genus Bifidobacterium, but from their carbohydrate fermentation patterns they did not appear to be strains of Bifidobacterium dentiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The data contained in this report should not be regarded as a precise definition of the cariogenic microflora associated with the tooth surfaces sampled. For example, we have isolated a variety of microorganisms, including Rothia dentocariosa, from both noncarious and carious sites (unpublished data) as well as dextranolytic strains of bifidobacteria from root lesions (12). Furthermore, the data presented here and in other studies of root caries (5,8,10,19,21) should not be considered entirely comparable because of differences in both the sampling and the culture methods.…”
Section: Discussionmentioning
confidence: 87%
“…The data contained in this report should not be regarded as a precise definition of the cariogenic microflora associated with the tooth surfaces sampled. For example, we have isolated a variety of microorganisms, including Rothia dentocariosa, from both noncarious and carious sites (unpublished data) as well as dextranolytic strains of bifidobacteria from root lesions (12). Furthermore, the data presented here and in other studies of root caries (5,8,10,19,21) should not be considered entirely comparable because of differences in both the sampling and the culture methods.…”
Section: Discussionmentioning
confidence: 87%
“…Bifidobacteria were probably not the main cause of this extended metabolism, as they were absent in water kefir B. Although there was no evidence for the degradation of the grain EPS, dextranase activity has already been shown in certain bifidobacterial (Kaster and Brown 1983) and LAB species (Picozzi et al 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Supportive of these findings, Mantzourani et al have also identified B. dentium, P. denticolens , and S. inopinata from the caries samples of primary teeth [ 61 ]. An intriguing characteristic shared by these species is their ability to degrade complex carbohydrates, including dextran [ 62 ] which potentiates the production of demineralizing acids within the cariogenic biofilm, even in the absence of fermentable carbohydrates [ 62 ]. Furthermore, another recent study has reported the synergism in acidogenicity in dual-species biofilms of P. denticolens, S. inopinata , and B. dentium , with S. mutans [ 63 ].…”
Section: Discussionmentioning
confidence: 99%